PHARMACEUTICAL KNOWLEDGE IN THE SAMANIDS EPOCH - A.R. NURIYON; S.D. YUSUFI (Avicenna Tajik State Medical University, 2017)
In this review, from a historical point of view, the state of pharmacology and pharmacy described in the era of the Samanid's. Studying the fundamental works of native and foreign authors allowed drawing a conclusion about a well high level of development of medicine and pharmacy in this period. A great contribution of scholars of the Samanid's era noted in the formation and further development of world medical science and pharmacy.